Slum tourism in the context of the tourism and poverty (relief) debate - Frenzel, Fabian (DIE ERDE: Journal of the Geographical Society of Berlin, 2013)
The paper examines the role of slum tourism in poverty relief. To do so, it surveys the state-of-the-art literature on tourism and poverty and investigates the ways in which slum tourism research relates to this literature. Slum tourism research has addressed the question of how the poor may benefit from this practice; however, these efforts have not systematically considered the general debate on tourism and poverty relief. The survey of slum tourism research also contributes to the conceptual development of the tourism-poverty nexus. The predominant choice of approaches in this field relies on quantitative indicators of poverty relief, but these do not sufficiently account for the multi-dimensional character of poverty. The study of slum tourism research points to the multi-dimensional valorisation of poverty in tourism which is an aspect often overlooked in the state-of-the-art research on tourism and poverty